Long shadows - Hunter, Erin. (New York, NY : Harper, an imprint of HarperCollins Publishers, 2015)
Three young cats from the Warriors clan face the ultimate test of their abilities as they struggle to protect the other clans from total destruction.
6.7
5-8
5-8
750L
750L
750L
Keywords: Cats -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Cats -- Fiction; Brothers and sisters -- Fiction; Cats -- Fiction; Siblings -- Fiction